A DIGITALISASI PEMBUKUAN UMKM TING ONE DRINK DENGAN APLIKASI BUKU WARUNG BERBASIS ANDROID: Digitalisasi, UMKM, Buku Warung - Fitri, Khoiriah Fitri (TALI JAGAD JOURNAL, 2025)
Abstract This research discusses the application of the Android-based Buku Warung application to digitize bookkeeping at Ting One Drink MSMEs in Medan. This application increases the efficiency of recording transactions, managing stock, and preparing financial reports. By reducing recording errors and speeding up the reporting process, this application also increases transparency and accountability. The research results show that business owners can make data-based decisions more quickly, focus on product development, and increase productivity. This digitalization of bookkeeping contributes to the ability of MSMEs to compete in the modern market and supports business sustainability. In addition, this research highlights the importance of technology in supporting the growth and development of MSMEs, and provides insight into how digital applications can be an effective tool in improving business performance.